Artificial Diets With Different Protein Levels for Rearing Spodoptera frugiperda (Lepidoptera: Noctuidae). Issue 4 (7th July 2021) - Truzi, Caio Cesar; Vieira, Natalia Fernanda; de Souza, Joice Mendonça; De Bortoli, Sergio Antonio
Abstract: Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae) is a pest of great economic importance which can feed on more than 300 plant species. As it is polyphagous, its host plants may have variable physical and chemical constitutions. This may influence larval development, as protein and carbohydrate levels are important factors for adequate biological development. The aim of this study was to evaluate insect developmental parameters as well as to compare the food consumption of S. frugiperda larvae reared using diets with different protein levels under laboratory conditions. Three artificial diet formulations were used: one typically used for routine laboratory rearing, based on bean, wheat germ and brewer's yeast (D1 ); one containing half the original amount of protein (D2 ), and the other with twice the original amount of protein (D3 ). The relative consumption rate (RCR), relative growth rate (RGR), and efficiency of conversion of ingested food (ECI) for S. frugiperda fourth instar larvae varied among diets. The protein present in the diet influenced the duration of larval and pupal periods and pupal weight, but did not affect larval survival, fecundity and longevity of adults. The different protein levels in the diets did not negatively influence population growth, so these three diet variations can be used for mass rearing in the laboratory. However, the influence of these diets on successive generations of the insect remains untested.